Chronic Medical Conditions and CA125 Levels among Women without Ovarian Cancer - Akinwunmi, Babatunde O.; Babic, Ana; Vitonis, Allison F.; Cramer, Daniel W.; Titus, Linda; Tworoger, Shelley S.; Terry, Kathryn L. (Cancer epidemiology, biomarkers & prevention, 2018)
Randomized trials using the biomarker cancer antigen (CA) 125, with or without pelvic ultrasound, have failed to show a clear benefit of general population screening for ovarian cancer. In part, this may be due to a lack of information about conditions, besides ovarian cancer, that can alter CA125 levels and affect specificity or sensitivity. We evaluated the association between common medical conditions and CA125 levels among women without ovarian cancer. We used data and specimens from 2,004 women without ovarian cancer who participated in the New England Case Control study between 1992 and 2008. Participants completed in-person interviews and donated blood samples at enrollment. We measured CA125 using the CA125II assay and calculated the association between medical conditions and log-transformed CA125 using linear regression. The median age of participants was 53 years and 1,119 (56%) were postmenopausal. The average CA125 level was 14.5 units/mL for premenopausal and 11.7 for postmenopausal women. Among premenopausal women, CA125 was significantly lower for women with colon polyps ( = 0.06) and hysterectomy ( = 0.01) and significantly higher with endometriosis ( = 0.05). CA125 was also significantly higher in premenopausal women with coronary artery disease (CVD) ( < 0.01, = 2 cases) but not among postmenopausal with CVD ( = 79). Furthermore, among postmenopausal women, CA125 was significantly lower for women with osteoporosis, hypercholesterolemia, and osteoarthritis ( = 0.03, 0.02, and 0.01 respectively) and higher for women with a history of inflammatory bowel disease ( = 0.04). Several chronic diseases are associated with CA125, which could influence the interpretation of CA125 in the context of ovarian cancer screening. Consideration of chronic medical conditions may be necessary to interpret CA125 values.